Ammonothermal Synthesis and Characterization of Li4[Zn(NH2)4](NH2)21. Issue 6 (24th March 2015) - Richter, Theresia M. M.; Alt, Nicolas S. A.; Schlücker, Eberhard; Niewa, Rainer
Abstract Single crystals of Li4[Zn(NH2)4](NH2)2 were obtained from Li and Zn under ammonothermal conditions (723 K and 1.58 kbar). Li4[Zn(NH2)4](NH2)2 (C2221, a = 5.0005(3) Å, b = 15.5410(8) Å, c = 10.0712(5) Å, Z = 4) represents a new possible intermediate in a conceivable ammonothermal synthesis of the semiconductor Zn3N2. Single crystal X‐ray diffraction results, thermal analysis, Raman and IR spectra of tetralithium tetraamido zincate diamide are provided and discussed. Crystal structure data justify a description as CaF2 superstructure variant. Large distances in the crystal structure as well as the intensity and half‐width of the bands in Raman and IR spectra indicate the absence of significant hydrogen bonds. Upon heating Li4[Zn(NH2)4](NH2)2 decomposes via intermediate formation of LiZnN, LiNH2 and Li2(NH) to finally provide pure Zn.